2019
DOI: 10.2174/1570180816666190701101734
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Insecticidal Evaluation and Modeling Studies on 1,4,6,7- tetrahydropyrazolo[3,4-d][1,3]oxazine Derivatives: An Application of Scaffold Hopping Strategy on Fipronil

Abstract: Background:: As the first phenylpyrazole pesticide, fipronil has been widely used in crop protection and public hygiene. In the low energy conformation of fipronil, a pseudo-six-membered ring is observed through an intramolecular hydrogen bond. Methods: : A scaffold hopping strategy was applied to mimic the pseudo-six-membered ring of fipronil by non-aromatic ring. All compounds were synthesized with a proper synthetic route and characterized by 1H NMR, 13C NMR and high-resolution mass spectra. Insecticidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For agrichemical fipronil, a N−H⋅⋅⋅O intramolecular hydrogen bond can be observed in the low energy conformation [22] . In our previous studies, as shown in Figure 2, two series compounds including aromatic and aliphatic rings mimic the pseudo six‐member ring conformed by intramolecular hydrogen bond (H‐Bond) in fipronil [10,23] . However, the insecticidal activities of these two series of compounds were inferior because of the losing of the amino hydrogen, which is a vital hydrogen bond donor in the binding mode of fipronil.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…For agrichemical fipronil, a N−H⋅⋅⋅O intramolecular hydrogen bond can be observed in the low energy conformation [22] . In our previous studies, as shown in Figure 2, two series compounds including aromatic and aliphatic rings mimic the pseudo six‐member ring conformed by intramolecular hydrogen bond (H‐Bond) in fipronil [10,23] . However, the insecticidal activities of these two series of compounds were inferior because of the losing of the amino hydrogen, which is a vital hydrogen bond donor in the binding mode of fipronil.…”
Section: Introductionmentioning
confidence: 92%
“…[22] In our previous studies, as shown in Figure 2, two series compounds including aromatic and aliphatic rings mimic the pseudo six-member ring conformed by intramolecular hydrogen bond (H-Bond) in fipronil. [10,23] However, the insecticidal activities of these two series of compounds were inferior because of the losing of the amino hydrogen, which is a vital hydrogen bond donor in the binding mode of fipronil. Considering the balance of toxicity and activities, there is a need for developing the phenylpyrazole insecticide leads preserving at least one amino hydrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation